KEBIJAKAN POLITIK ELECTRONIC GOVERNMENT, PELAYANAN PUBLIK ATAU KEPENTINGAN POLITIS ? (STUDI DESKRIPTIF IMPLEMENTASI E-KTP DI KOTA SURABAYA) - Dwi Wahyu Prasetyono; Putu Aditya Ferdian Ariawantara (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
ICT (Information and Communication Technology) has a goal to create an electronic-based government, which is expected to produce public service a fair, transparent, efficient, and the benefits felt by all citizens without exception. One form of public service as a result of the development of electronic government is the e-ID (Electronic Identity Card). Approaches or methods used by researchers is a qualitative approach to the type of research is descriptive, because the purpose of this study was to determine the implementation of e-ID cards in the city of Surabaya and to seeing whether the implementation of electronic government policy be used to facilitate public services, or simply as a tool for political purposes certain. The creation of the accuracy of population data to support development programs (in e-ID); Can be used as a data base in the elections to prevent double voting list. In the implementation in the field, district officers and officials assembled in the region (eg Department of Population and Civil Surabaya City) can not innovate in developing e-ID service, because there has been SOP from the main government.